Pengembangan Jati Diri untuk Membangun Karakter Seseorang Melalui Niat dan Dorongan untuk Mencapai Tujuan (International Forum of Researchers and Lecturers, 2025)
Developing identity is one of the fundamental elements in building a person's character. Strong character plays an important role in facing various life challenges, both in the family, education and community environments. One aspect that can lead to optimal development of identity is through intention and encouragement to achieve clear life goals. Sincere intentions and strong drive are the driving forces that will help individuals stay focused and consistent in achieving their goals, even when faced with various obstacles and temptations. In this context, a well-defined life goal not only provides direction, but also provides deep meaning in every step taken by the individual. The process of developing identity, which is influenced by intentions and encouragement, is closely related to character formation. The character that is formed is not only visible from a person's attitudes and behavior, but also from the ability to manage emotions, make wise decisions, and be responsible for the actions taken. Over time, developing your identity will increase self-confidence, strengthen mental resilience, and foster a sense of responsibility towards yourself and others. This article aims to explain the importance of intention and drive in developing one's identity to build one's character, as well as how this process is related to achieving larger life goals. In its implementation, a supportive environment such as family, school and community plays a significant role in forming and strengthening a person's identity. Character education, in this case, has an important role in guiding individuals to develop positive intentions and providing the encouragement needed to achieve their life goals. Therefore, it is important for each individual to have strong intentions and the right encouragement in the process of developing their identity, in order to achieve life goals that are in line with positive values ​​that can enrich their lives and those of the surrounding community.